An exploratory study on tonnage tax adoption in Nigerian shipping industry - Baba, Jibril, Zakari (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2022)
Tonnage tax regime has been adapted in several climes to address fleet-decline. The regime first started from Greece in 1975 and has diffused to jurisdictions across the globe. This regime considers gross/net tonnage of a ship as a tax-base unlike income tax-base in IFRS12. Nigeria current tax system was argued by numerous studies as unfriendly to shipping and among the reasons of fleet-decline. This study was conducted to understand the endogenous and exogenous drivers of the regime, its harmonisation process with IFRS, and to proffer the likely suitable regime from contents of other competitive shipping tax regimes. A face-to-face interview with experts in Nigerian shipping, focus-group interview with participants from Financial Reporting Council of Nigerian, and contents analysis of three international shipping-tax-consultants’ records (consisting of 56 countries were sampled) were conducted. Results were thematically presented into four areas using ATLAS.ti8. Top-management role, followed by employees, and the organisation were found as endogenous drivers in the regime. Secondly, the exogenous consideration was found social factor as the most critical, followed by economic factor, technological factor, environmental factor, and legal factor. Thirdly, on harmonisation with IFRS, two processes were identified: either initiation from local jurisdiction or umbrella body and the study found that standard or guidelines need to be developed before adoption. The last area explores other tax regimes and establishes the likelihood of adoption, where tonnage tax was found as the most occurred in the content reviewed. Limitation includes reliance on the participants’ ability to accurately and honestly recall their experiences, circumstances, thoughts or behaviours during the interview. Originality: The method employed is a flexible and powerful tool that enables capturing of participants voices and the meanings they make from their experiences as experts in Nigeria shipping industry. The findings reveal a deep understanding of the issues from field-experts view.